2008
DOI: 10.5688/aj7206147
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Peer Teaching-Assessment Program and a Peer Observation and Evaluation Tool

Abstract: Objectives. To develop a formalized, comprehensive, peer-driven teaching assessment program and a valid and reliable assessment tool. Methods. A volunteer taskforce was formed and a peer-assessment program was developed using a multistep, sequential approach and the Peer Observation and Evaluation Tool (POET). A pilot study was conducted to evaluate the efficiency and practicality of the process and to establish interrater reliability of the tool. Intra-class correlation coefficients (ICC) were calculated. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 18 publications
3
70
1
Order By: Relevance
“…A formal peer observation and evaluation program for classroom teaching was developed and implemented by this department in January 2008, and the development of its process and the peer observation and evaluation tool (POET) have been previously published. 7 Two years after implementing the peer observation and evaluation process, the program was formally assessed. The objectives of this study were to determine: (1) faculty attitudes regarding peer observation and evaluation at 1 both pre-and post-implementation points; (2) the degree of adherence among faculty members to the peer observation and evaluation policies and procedures; (3) the type and nature of peer observation and evaluation feedback received; and (4) faculty perceptions of the peer observation and evaluation program's value and impact on their teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A formal peer observation and evaluation program for classroom teaching was developed and implemented by this department in January 2008, and the development of its process and the peer observation and evaluation tool (POET) have been previously published. 7 Two years after implementing the peer observation and evaluation process, the program was formally assessed. The objectives of this study were to determine: (1) faculty attitudes regarding peer observation and evaluation at 1 both pre-and post-implementation points; (2) the degree of adherence among faculty members to the peer observation and evaluation policies and procedures; (3) the type and nature of peer observation and evaluation feedback received; and (4) faculty perceptions of the peer observation and evaluation program's value and impact on their teaching.…”
Section: Introductionmentioning
confidence: 99%
“…The content and process of the program and the content of the POET are described in more detail in a previous publication. 7 All faculty members hired prior to 2008 were required to undergo peer evaluation of 1 lecture annually. All faculty members who received training were also asked to serve as peer observers.…”
mentioning
confidence: 99%
“…35 Several colleges and schools of pharmacy include faculty member peer reviews of classroom teaching. [38][39][40] used in conjunction with student teaching evaluations, peer reviews often serve as another summative measure for promotion and tenure decision-making. Turpen et al indicated in preliminary findings that even when institutions used both student teaching evaluations and peer reviews, they tended to rely on student teaching evaluations only for faculty performance evaluations.…”
Section: Formative Assessment Of Faculty Teachingmentioning
confidence: 99%
“…9 Many models have emerged for peer review of teaching. 2,3,5,6,7,9,10,11,12,13,14,15,16,17,18,19,20 The following variations are all described in the literature: classroom observation alone (may be a single visit or multiple visits), or a more comprehensive review of materials including student work, assessment, and syllabi; feedback tools may include simple checklists, rating scales, written feedback, and/or verbal feedback; reviewers may or may not receive specialized training; reviewers may consist of a small group of individuals chosen for the task or pairs that agree or are selected to conduct reciprocal reviews; and pre-and/or post-observation meetings may be included. Given this variation, it is not clear that benefits attributed to peer review are generalizable in all contexts.…”
Section: Introductionmentioning
confidence: 99%